Analisis Strategi Pemasaran Dalam Menarik Minat Beli Konsumen Melalui Media Sosial Di CV Jasa Gambar Bangunan Probolinggo - Prasetyo, Bagus; Widarko, Agus; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze marketing strategies through social media used to attract consumer buying interest at CV Jasa Gambar Bangunan Probolinggo. This study uses a descriptive qualitative method. The informants in this study consisted of 7 informants who had been determined using purposive sampling techniques. Data collection methods in this study consisted of observation, interviews and documentation. Data analysis of this study used segmentation, targeting, positioning and marketing mix analysis techniques. The results of this study indicate that the marketing strategy implemented by CV Jasa Gambar Bangunan Probolinggo has been running quite well in attracting consumer buying interest. However, the effectiveness and efficiency of the strategy are still not optimal. Keywords: Marketing Strategy, Social Media, Consumer Buying Interest